2013
DOI: 10.3390/ijms140917453
|View full text |Cite
|
Sign up to set email alerts
|

The Characterisation of Pluripotent and Multipotent Stem Cells Using Fourier Transform Infrared Microspectroscopy

Abstract: Fourier transform infrared (FTIR) microspectroscopy shows potential as a benign, objective and rapid tool to screen pluripotent and multipotent stem cells for clinical use. It offers a new experimental approach that provides a holistic measurement of macromolecular composition such that a signature representing the internal cellular phenotype is obtained. The use of this technique therefore contributes information that is complementary to that acquired by conventional genetic and immunohistochemical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 47 publications
2
30
0
1
Order By: Relevance
“…Zelig et al (2009) found that this scenario to be associated with apoptotic cells [29]. [49] Other vibrational bands associated with cytotoxicity was also detected in the cells treated with 18 µg/mL (Fig. 4, the vibrational mode of the C-O-C ring of deoxyribose in Z-form DNA [37,38,44].…”
Section: Early Stress Related Responses and Cytotoxicitymentioning
confidence: 99%
“…Zelig et al (2009) found that this scenario to be associated with apoptotic cells [29]. [49] Other vibrational bands associated with cytotoxicity was also detected in the cells treated with 18 µg/mL (Fig. 4, the vibrational mode of the C-O-C ring of deoxyribose in Z-form DNA [37,38,44].…”
Section: Early Stress Related Responses and Cytotoxicitymentioning
confidence: 99%
“…5. An absorption band at 1745 cm −1 is related to the stretching vibration of C=O ester group of lipids [21], while two intense bands at 1650 and 1540 cm −1 are related to amide I and amide II functional groups of proteins respectively [22]. Another band at 1454 cm −1 arises from the methyl and methylene groups from lipids and proteins, whereas the band at 1396 cm −1 is due to the COO − stretching vibrations of amino acid side chains [21].…”
Section: Resultsmentioning
confidence: 99%
“…An absorption band at 1745 cm −1 is related to the stretching vibration of C=O ester group of lipids [21], while two intense bands at 1650 and 1540 cm −1 are related to amide I and amide II functional groups of proteins respectively [22]. Another band at 1454 cm −1 arises from the methyl and methylene groups from lipids and proteins, whereas the band at 1396 cm −1 is due to the COO − stretching vibrations of amino acid side chains [21]. The band at 1239 cm −1 is related to the P=O asymmetrical stretching of PO 2 phosphodiester groups from phosphorylated molecules, whereas the band at 1080 cm −1 arises from the P=O symmetrical stretching of PO 2 phosphodiester groups from phosphorylated molecules and glycogen [21, 23].…”
Section: Resultsmentioning
confidence: 99%
“…y Cao y cols. [8,9] , los espectros FTIR obtenidos en este trabajo de CMP y CPD fueron complejos, pero el uso del análisis multivariado nos facilitó el procesamiento para identificar y evidenciar los cambios espectrales más significativos durante la diferenciación; en nuestro caso, la segunda derivada de los espectros de CMP y CPD (Figura 4), fue utilizada para proporcionar mayor precisión al ACP.…”
Section: Espectroscopía Infrarroja Por Transformada De Fourierunclassified